Evaluation Model of the Management Zakat Profession of the State Civil Apparatus (ASN) by the National Amil Zakat Agency (BAZNAS) of Bandung - Maya Kusuma Permata Sari; Didin Muhafidin; R. Achmad Buchori (GoAcademica Research & Publishing, 2019)
This study aims to determine the evaluation model of zakat management for the civil servant by the National Amil Zakat Agency (BAZNAS) in the city of Bandung. Qualitative research methods used are needed data related to the evaluation of professional zakat management by using a set of open and flexible question lists from formulation of the problem regarding assessment of civil servant professional zakat management in the National Amil Zakat Agency (BAZNAS) of Bandung, to be explained, described, investigated and understood overall problem that occurs. The results showed that the evaluation model of zakat management of the Bandung City Civil Servants (ASN) profession was carried out by the Bandung City BAZNAS, as a planner, executor, and coordinator in the collection and utilization of zakat. The Zakat Collecting Unit (UPZ), whose task is to collect professional zakat from ASN, uses the Official Assessment system through salary deductions made by the Salary Treasurer. The process, benefits, and impacts relating to the pattern of receipt and distribution of professional zakat are carried out by delegating management authority and responsibility for the payment of the National Amil Zakat Agency (BAZNAS) and distributing professional zakat to the entitled parties, 8 Ashraf both consumptive and productive. in the form of venture capital. Keywords: Managmenet Evaluation Model, Zakat Profession, Civil Servant (ASN), National Amil Zakat Agency (BAZNAS).